Case report: Central nervous system involvement of human graft versus host disease. Issue 42 (October 2017) - Ruggiu, Mathilde; Cuccuini, Wendy; Mokhtari, Karima; Meignin, Véronique; Peffault de Latour, Régis; Robin, Marie; Fontbrune, Flore Sicre de; Xhaard, Aliénor; Socié, Gérard; Michonneau, David
Abstract: Rationale: Central nervous system (CNS) involvement of graft versus host disease (GvHD) is a rare cause of CNS disorders after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Chronic CNS GvHD symptoms are heterogeneous and include cerebrovascular manifestations, demyelinating disease and immune-mediated encephalitis. CNS-Acute GvHD is not formally defined in literature. Patients concerns and diagnoses: We report 7 cases of CNS-GvHD among which two had histological-proven disease. We reviewed 32 additional cases of CNS GvHD published in literature since 1990. In this cohort, 34 patients were transplanted for hematologic malignancies, and 5 for non-malignant hematopoiesis disorders. Of these patients, 25 had a history of chronic GvHD and immunosuppressive treatment had been decreased or discontinued in 14 patients before neurological symptoms onset. Median neurological disorder onset was 385 days [7-7320]. Patients had stroke-like episodes (n = 7), lacunar syndromes (n = 3), multiple sclerosis-like presentations (n = 7), acute demyelinating encephalomyelitis-like symptoms (n = 4), encephalitis (n = 14), mass syndrome (n = 1), and 3 had non-specific symptoms. Median neurological symptoms onset was 81.5 days [7-1095] for patients without chronic GVHD history versus 549 days [11-7300] for patients with chronic GVHD ( P  = 0.001). Patients with early involvement of CNS after allo-HSCT and no chronic GVHD symptoms were more frequently suffering from encephalitis (64% versus 28%, P  = 0.07), whereas stroke-like episodes and lacunar symptoms were less frequent (9% versus 36%, P  = 0.13). Interventions: 34 patients with CNS-GvHD were treated with immunosuppressive therapy, including corticosteroids for 31 of them. Other treatments were intravenous immunoglobulin, plasmapheresis, cyclophosphamide, calcineurin inhibitors, mycophenolic acid, methotrexate and etoposide. Outcomes: 27 patients achieved a response: 10 complete responses, 15 partial responses and 2 transient responses. Of 25 patients with sufficient follow-up, 7 were alive and 18 patients deceased after CNS-GvHD diagnosis. Lessons: CNS-related GvHD is a rare cause of CNS disorders after allo-HSCT and is associated with a poor prognosis.